PROPOSED CONCEPTUAL FRAMEWORK FOR STUDYING NON-USERS RICE FARMERS' INTENTION TO USE COMMERCIAL BIOPESTICIDES PRODUCTS - Istriningsih; Sumarwan, Ujang; Hartoyo; Suharjo, Budi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2023)
Commercial biopesticide products have been developed for a long time in Indonesia, but until now the level of application is still relatively low. This paper aims to determine the factors that are expected to influence the intention of non-users rice farmers to use commercial biopesticide products. Furthermore, a conceptual framework of intention to use commercial biopesticide products is proposed. Based on the literature review of previous empirical studies in various contexts, this paper has explored the factors that influence the intention of using biopesticides. Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) is employed as the main theoretical basis in this study which can be extended with relevant constructs to the research context (extended UTAUT2). The proposed conceptual framework recommends that non-users rice farmers' intention to use commercial biopesticide products is expected to be influenced by variables namely performance expectancy, effort expectancy, social influence, facilitating condition, price value, perceived need, information publicity, and product marketing. This integrative conceptual framework is expected to have a theoretical contribution to understand the factors of non-users rice farmers’ intention to use commercial biopesticide products. In addition, it is beneficial for policymakers and managers to formulate and implement strategies to increase rice farmers' intention to use commercial biopesticide products.